Digoxin use in patients with atrial fibrillation and adverse cardiovascular outcomes: a retrospective analysis of the Rivaroxaban Once Daily Oral Direct Factor Xa Inhibition Compared with Vitamin K Antagonism for Prevention of Stroke and Embolism Trial in Atrial Fibrillation (ROCKET AF). Issue 9985 (13th June 2015) - Washam, Jeffrey B; Stevens, Susanna R; Lokhnygina, Yuliya; Halperin, Jonathan L; Breithardt, Günter; Singer, Daniel E; Mahaffey, Kenneth W; Hankey, Graeme J; Berkowitz, Scott D; Nessel, Christopher C; Fox, Keith A A; Califf, Robert M; et al.
Summary: Background: Digoxin is a widely used drug for ventricular rate control in patients with atrial fibrillation (AF), despite a scarcity of randomised trial data. We studied the use and outcomes of digoxin in patients in the Rivaroxaban Once Daily Oral Direct Factor Xa Inhibition Compared with Vitamin K Antagonism for Prevention of Stroke and Embolism Trial in Atrial Fibrillation (ROCKET AF). Methods: For this retrospective analysis, we included and classified patients from ROCKET AF on the basis of digoxin use at baseline and during the study. Patients in ROCKET AF were recruited from 45 countries and had AF and risk factors putting them at moderate-to-high risk of stroke, with or without heart failure. We used Cox proportional hazards regression models adjusted for baseline characteristics and drugs to investigate the association of digoxin with all-cause mortality, vascular death, and sudden death. ROCKET AF was registered with ClinicalTrials.gov, number NCT00403767 . Findings: In 14 171 randomly assigned patients, digoxin was used at baseline in 5239 (37%). Patients given digoxin were more likely to be female (42% vs 38%) and have a history of heart failure (73% vs 56%), diabetes (43% vs 38%), and persistent AF (88% vs 77%; p<0·0001 for each comparison). After adjustment, digoxin was associated with increased all-cause mortality (5·41 vs 4·30 events per 100 patients-years; hazard ratio 1·17; 95% CI 1·04–1·32; p=0·0093), vascular death (3·55 vs 2·69 per 100 patient-years; 1·19; 1·03–1·39, p=0·0201), and sudden death (1·68 vs 1·12 events per 100 patient-years; 1·36; 1·08–1·70, p=0·0076). Interpretation: Digoxin treatment was associated with a significant increase in all-cause mortality, vascular death, and sudden death in patients with AF. This association was independent of other measured prognostic factors, and although residual confounding could account for these results, these data show the possibility of digoxin having these effects. A randomised trial of digoxin in treatment of AF patients with and without heart failure is needed. Funding: Janssen Research & Development and Bayer HealthCare AG.